x+x-2+x+1=62

Simple and best practice solution for x+x-2+x+1=62 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+x-2+x+1=62 equation:


Simplifying
x + x + -2 + x + 1 = 62

Reorder the terms:
-2 + 1 + x + x + x = 62

Combine like terms: -2 + 1 = -1
-1 + x + x + x = 62

Combine like terms: x + x = 2x
-1 + 2x + x = 62

Combine like terms: 2x + x = 3x
-1 + 3x = 62

Solving
-1 + 3x = 62

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 3x = 62 + 1

Combine like terms: -1 + 1 = 0
0 + 3x = 62 + 1
3x = 62 + 1

Combine like terms: 62 + 1 = 63
3x = 63

Divide each side by '3'.
x = 21

Simplifying
x = 21

See similar equations:

| 8x^2-4x-60=0 | | 6x-14=6x+6-3x | | 10+2x=328 | | 6x-14=8x+8-3x | | 6x-14=5x+5-3x | | 7x-2=-3x | | 2w^2-3w-90=0 | | 5n-2=3n+6 | | 2a-[(3a+4)-5]-a=5 | | 19+7n-5+6n=8n+7+3n-19 | | (x+126)(x+120)=0 | | 2(5g-3)-6(g-7)=g+6(g+7) | | 10y-20=-4y+6 | | 4y-2+3=-2y-4 | | -4(7n-4)+4n= | | 11-(7a-a)+11a=4(3a+7) | | 20(31)= | | 8x-11y=32 | | 2y+5x=6 | | x+494=2753 | | 3(8n-2)-3(1-n)+8=8 | | 2x+2j=1-yj | | 5[x-4(4x-5)]=3-2x | | 3y+7=16 | | (2-4j)x+9+(1+4j)=0 | | -3n-2+6n=7n+26 | | 2.97=x+1.6 | | r+.07r=506 | | -3(2y+4)= | | -25x^2+1=0 | | y-4.7=12.52 | | (6c-7d)-(3c+6cd)= |

Equations solver categories